ChemInform Abstract: One Step Synthesis of Highly Functionalized Thiazolo[3, 2‐b][1, 2, 4]triazole, Triazolo[1, 5‐a]pyrimidine and Triazolo[3, 4‐b][1, 3, 4]thiadiazine. Issue 18 (April 2016) - Shah, Tariq A.; Ahmad, Zubair; Mir, Niyaz A.; Muneer, M.; Rath, Nigam P.; Ahmad, Musheer
Abstract: The reaction of dibenzoylacetylene with triazoles gives the title compounds with excellent yields via a catalyst‐free one‐pot cyclization at room temperature.